The Natamycin Preservation of the Laboratory produced cheese against spoilage of Yeasts & Moulds: Ahmed M.S. Al-Shdidi Muna M. Ismaeel Rafid S. A. Al-Zubaidy - Al-Shdidi, Ahmed M.S. (The Iraqi Journal of Veterinary Medicine, 2011)
The study conducted an attempts to improve the Keeping quality (Shelf T.) of Laboratory processed cheeses by the Natamycin preservation against spoilage of Yeasts & Moulds . Random collected samples of processed soft cheeses collected from different areas of Baghdad to produce Laboratory processed cheeses by using the best mix of Emulsifying salts that is composed of :- 90% Na tripolyphosphate + 10% 3Na citrate . Laboratory processed cheeses without preservative treating lasted to be fit for humane consumption for (30) day when store at room temp. & aerobic Condition & for (45) day when store at room temp. & non aerobic condition & for (40) day when store at refrigeration temp. & aerobic condition & for (60) day when store at refrigeration temp. & non aerobic condition.While the Laboratory processed cheeses which treated with Natamycin lasted to be fit for humane consumption for (35) day when store at room temp. & aerobic condition & for (45) day when store at room temp. & non aerobic condition & for (40) day when store at refrigeration temp. & aerobic condition & for (60) day when store at refrigeration temp. & non aerobic condition . Such finding of high concentration of Yeasts & Moulds count ides to the fact that the use of Preservative lead to Prolongation Shelf time of Dairy products depending on storing temperature at (room or refrigeration) & depending on storing condition by (aerobic or non aerobic) . Results showed that such cheese of low quality and did not meet both local and international Dairy products standards and unfit for human consumption .